Towards the Exploitation of Data 4.0 in Health Environments - Tellería, Carlos; Ilarri, Segio; Bernal, Enrique (Jornada de Jóvenes Investigadores del I3A, 2019)
Designing appropriate techniques and methodologies to exploit Real-World Health Data is essential to improve the performance and sustainability of health systems, the well-being of patients, and the value of the data collected. In this short paper, we briefly describe the main goals that we intend to tackle in this area